Improving Local Wisdom and Local Culture in the 5.0 Era - Wahdiniawati, Siti Annisa; Jatmiko Murdiono; Rita Mulyanti; Nurhayati (Dinasti Information and Technology, 2023)
The purpose of this paper is to increase understanding of the importance of strengthening and preserving local wisdom and culture in the 5.0 Era, while also making readers aware of the challenges faced, identifying workable solutions, advocating for cultural education, encouraging intercultural collaboration, supporting sustainable development, and promoting the wise use of technology in the context of preserving local wisdom and culture. The importance of maintaining and developing traditional values in the face of technological advances. The 5.0 era brings challenges and opportunities, but local wisdom remains relevant for sustainability and cultural identity. The recommendation given is to create an environment that supports the preservation and development of local wisdom, while bridging the gap between tradition and innovation of the 5.0 era